Thermodynamic Evaluation and Carbon Footprint Analysis of the Application of Hydrogen‐Based Energy‐Storage Systems in Residential Buildings. Issue 3 (4th November 2016) - Adametz, Patrick; Pötzinger, Christian; Müller, Stefan; Müller, Karsten; Preißinger, Markus; Lechner, Raphael; Brüggemann, Dieter; Brautsch, Markus; Arlt, Wolfgang
Abstract: This study represents a thermodynamic evaluation and carbon footprint analysis of the application of hydrogen‐based energy storage systems in residential buildings. In the system model, buildings are equipped with photovoltaic (PV) modules and a hydrogen storage system to conserve excess PV electricity from times with high solar irradiation to times with low solar irradiation. Short‐term storages enable a degree of self‐sufficiency of approximately 60 % for a single‐family house (SFH) [multifamily house (MFH): 38 %]. Emissions can be reduced by 40 % (SFH) (MFH: 30 %) compared to households without PV modules. These results are almost independent of the applied storage technology. For seasonal storage, the degree of self‐sufficiency ranges between 57 and 83 % (SFH). The emission reductions highly depend on the storage technology, as emissions caused by manufacturing the storage dominate the emission balance. Compressed gas or liquid organic hydrogen carriers are the best options, enabling emission reductions of 40 %. Abstract : Hydrogen storages in action ! The potential of different hydrogen storage technologies as energy storages in residential buildings is evaluated. For short‐term storage, system performance is almost independent of the storage technology. Degrees of self‐sufficiency up to 60 % and emission reductions up to 40 % are possible. For seasonal storage, system performance is highly dependent on the storage technology, especially the emissions reduction potential. PV=photovoltaic.